FAKTOR-FAKTOR YANG MEMENGARUHI RESILIENSI KELUARGA TERHADAP BENCANA BANJIR DI KELURAHAN CEMPAKA BARU JAKARTA PUSAT - Vidya Hanan Hafizha (2020)
Resilience built when a person or a family faces adversity to survive in the present situation, or that will even thrive in the future. A disaster is also seen as an adversity someone might meet in their life. This study uses a cross-sectional design to analyze factors that may affect a family's resilience towards flood hazards in the subdistrict of Cempaka Baru Central Jakarta. This study involved 270 families in participating in the survey. Questionnaires are used to measure proactive coping, risk perception, preparedness behavior, and family resilience towards flood hazards, which has been tested for validity and reliability. The results show that there are associations between proactive coping (P =.039), risk perception (P <.001), and the family's preparedness behavior (P < .001) to the family resilience towards flood hazards. The level of education of the head of the family, family's income, the number of the family members, and the number of vulnerable groups in the family have a significant association with family resilience (P = .003).